1970
DOI: 10.1002/1097-0142(197011)26:5<1053::aid-cncr2820260513>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Papillary carcinoma of the thyroid I. Developing pattern of metastasis

Abstract: Seventy‐one cases of papillary adenocarcinoma of the thyroid were operated on from January 1967 to July 1968. in 14 cases, the diagnosis of carcinoma was established postoperatively, so that 57 patients underwent systematic lymph node excision. Among these 57 cases, 90% had evidence of metastasis. a majority of metastatic deposits were small, i.e., 57% of them were less than 3 mm in diameter. There was no relationship between the location of primary tumor and metastasis; the initial metastases were most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0
9

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(159 citation statements)
references
References 10 publications
6
142
0
9
Order By: Relevance
“…As in previous studies, papillary thyroid carcinoma had been known to be more commonly found with cervical lymph node metastases than follicular carcinoma (Coburn & Wanebo 1992, Sellers et al 1992). From 63 to 80% of papillary thyroid carcinoma patients had micrometastases (Noguchi et al 1970, Attie et al 1972. Most of these micrometastases were clinically insignificant (Sellers et al 1992).…”
Section: Discussionmentioning
confidence: 54%
“…As in previous studies, papillary thyroid carcinoma had been known to be more commonly found with cervical lymph node metastases than follicular carcinoma (Coburn & Wanebo 1992, Sellers et al 1992). From 63 to 80% of papillary thyroid carcinoma patients had micrometastases (Noguchi et al 1970, Attie et al 1972. Most of these micrometastases were clinically insignificant (Sellers et al 1992).…”
Section: Discussionmentioning
confidence: 54%
“…LN metastasis can appear in several levels and skip metastasis frequently occurs (Mirallie et al 1999). The correlation between the sites of LN metastasis and the tumor location within the thyroid is not consistent (Noguchi et al 1970). The rate of positive LN detection increases by immunohistochemical staining compared with H&E staining (Qubain et al 2002).…”
Section: Ln Controlmentioning
confidence: 99%
“…Some authors have reported that each lobe of the thyroid gland has its own internal lymphatic system, and there is no communication with contralateral regional lymph nodes 14,15) (although PTC can spread to regional lymph nodes bilaterally [16][17][18] ) It has been generally accepted that lymphatic drainage occurs from the thyroid primarily to the central lymphatic compartment and secondarily to the lateral compartment nodes. 19,20) As a result, locoregional spread of thyroid cancer predominantly involves the ipsilateral, and sometimes also the contralateral central and lateral neck nodes. [21][22][23][24] Dralle and Machens 25) suggested that lymphatic tumor cell dissemination is modulated by the anatomical location of the primary thyroid tumor.…”
Section: Lymphatic Drainage Of the Thyroidmentioning
confidence: 99%